BIOLOGY OF SPHEDANOLESTES PUBINOTUM REUTER (HETEROPTERA : REDUVIIDAE) A POTENTIAL PREDATOR OF INSECT PESTS - KUMARASWAMI, N. SELVAMUTHU; PAMBROSE, DUNSTON (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
S. pubinorum Reuter a potential predator of insect pests laid its first batch of eggs 11.66 EO.88 days after imaginal moult. A female laid on an average 54.0+5.4 eggs. The hatching percentage was 81.45+ 4.66. Nymphal period ranged from 42 to 68 days. A key for nymphal instars was also prepared for their identification. The highest nymphal mortality was observed in the II nymphal instars. Adult female lived longer than the male. The sex ratio was female biased.